Improving Students' Social Interaction through Nojapi-Japi Traditional Game at SD Negeri Kele'I: English - Andi Imrah Dewi; Delviana Kristina Wendur; Arif Firmansyah; Kadek Hariana (Elementary Teacher Education Program, Majalengka University, 2024)
The decline in academic achievement and student social interaction is partly due to the excessive use of technology by students at school and at home. In order to maintain social interaction in the classroom and ensure students are more familiar with the culture around them, the influence of changes in modern technology must be balanced with traditional learning media. However, this study identified a low social interaction of students in learning in class IV SDN Kele'I East Pamona District. The research method employed was classroom action research based on the Kemmis and McTaggart flow. The objective of this study was to enhance students' social interaction in social studies subjects in class IV SDN Kele'i by implementing the traditional game nojapi-japi. This study utilized class IV SDN Kele'i, which comprised 20 individuals, including 11 female students and 9 male students. Data collection was conducted on student and teacher activities. The results of the study indicated that 70% of students demonstrated sufficient social interaction skills, 25% exhibited limited skills, and 5% displayed very poor skills. The overall average score for Cycle I was 62.25%. Therefore, it was deemed necessary to continue the study in Cycle II. The results of the second cycle of the study indicated that 30% of students exhibited exemplary social interaction skills, 45% demonstrated proficient social interaction abilities, and 25% demonstrated satisfactory social interaction skills, with an average score of 82.75%.